The Impacts of the Covid-19 Pandemic on Social Welfare Policies of Norway and Japan: A Comparative Study - Chum, Sopheakneat (Journal of Social Policy, Social Change and Development, 2023)
The impact of Covid-19 posed major challenges for governments, particularly in terms of welfare policies. This comparative analysis will mainly study the consequence of the pandemic on the social welfare policies of two nations, Norway and Japan, and define the similarities and differences in their policy responses in relation to the governments’ interest. The study focuses on a comparative study of the history of welfare state development, welfare provision, welfare financing, and welfare systems by the two countries in response to the pandemic. Data collection is significantly utilized from secondary data, including the review of official documents, news articles, media reports, and academic literature. The result of the study implies that both countries have made significant efforts to support individuals and businesses affected by the pandemic. Their policy responses differ in terms of scope, implementation, and outcome. Norway's policy response has been characterized by a significant expansion of its welfare state, including the provision of financial assistance to individuals, businesses, and local governments. In contrast, Japan's policy response has been more targeted and focused on supporting specific sectors and vulnerable groups, such as small and medium-sized enterprises and low-income households. Furthermore, the study highlights the role of institutional factors in shaping policy responses to the pandemic. Norway's strong social democratic tradition and well-established welfare state has enabled it to respond more effectively to the crisis, while Japan's more conservative political culture and fragmented welfare system have hindered its ability to implement comprehensive policy measures. Overall, the study contributes to our understanding of the impact of the pandemic on social welfare policies and the role of institutional factors in shaping policy responses. It provides insights for policymakers and scholars interested in understanding the challenges and opportunities for social welfare policies in the context of the ongoing pandemic.